Investigating one-to-one instrumental music lessons in relation to a training programme on Paul Harris’ simultaneous learning. - Mateos-Moreno, Daniel; Erlanson, Ernst (SAGE, 2024)
‘Simultaneous Learning’ (SL) is a pedagogical approach aimed at fostering enjoyable and proactive music teaching. Developed by the British educationalist Paul Harris, SL has been taught worldwide for the past two decades but has not yet been investigated by a scholarly publication. We thus focused our research on the first usage of SL in the context of one-to-one instrumental music lessons by training a selected group of teachers who had no prior experience with this approach. The data was collected through in-depth semi-structured interviews, focus group interview and journals kept by the teachers. We then used Interpretative Phenomenological Analysis (IPA) to understand the teachers’ and students’ experiences of instructing and being instructed according to the SL approach, respectively. Based on our results, we provide a structure to their lived experiences and explore the meanings they attached to them, among which positive experiences, challenges and the influence of SL on particular skills are identified. Furthermore, we offer implications that may benefit studio music tuition based on the insights provided by our analyses.
Keywords: Investigación activa en educación; Música - Estudio y enseñanza; Harris; Learning; Music; Simultaneous; Teaching